A vanadium battery diaphragm combination with a three-layer membrane structure and a preparation method thereof
By adopting a three-layer film structure in the vanadium battery separator, combining the technology of water-soluble polymer modified polyvinylpyrrolidone and microfiltration membrane, the existing vanadium battery separator has solved the low ion conductivity, high cost and positive and negative electrode vanadium. The problem of ion inter-serialization achieves high ion selectivity, long-term stability and low-cost separator performance.
Patent Information
- Application Number
- CN202411419281.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing vanadium battery separators have problems such as low ion conductivity, high cost, insufficient chemical stability, and capacity attenuation caused by inter-sertion of positive and negative electrode vanadium ions.
Using a three-layer membrane structure vanadium battery separator combination, a membrane modification method is formed to repel vanadium ions by combining the sieving effect of water-soluble polymer-modified polyvinylpyrrolidone and microfiltration membrane. And the pore size screening of the microfiltration membrane prevents the vanadium ions from being connected.
The ion selectivity, long-term cycle stability and mechanical properties of the membrane are improved, the electrode inert problem caused by desorption of polymer additives is avoided, and the cost of the membrane is reduced.
Smart Images

Figure CN118919754B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-vanadium liquid flow battery diaphragm, and in particular to a vanadium battery diaphragm assembly with a three-layer membrane structure and a preparation method thereof. Background Art
[0002] All-vanadium liquid flow battery (abbreviated as vanadium battery) is the most promising large-scale energy storage technology at this stage. It has the advantages of free site selection, controllable capacity, deep discharge, low self-discharge, high efficiency and good safety, and is increasingly attracting widespread attention from the society. Vanadium batteries are mainly composed of electrode materials, bipolar plates, electrolytes and diaphragms. Among them, the diaphragm, as one of the core components of vanadium batteries, should have excellent ion conductivity, high ion selectivity, excellent mechanical and chemical stability, low cost and other characteristics. Commercial porous membranes are widely used in water treatment and other fields, but there is a problem of low ion conductivity when used in vanadium batteries, and anion exchange membranes generally require a complex preparation process and have low coulombic efficiency. At present, perfluorosulfonic acid proton exchange membranes have become the most widely used diaphragms for vanadium batteries due to their excellent electrochemical properties and chemical stability, but this type of proton exchange membrane also has the problem of capacity attenuation caused by the mutual cross-talk of positive and negative vanadium ions. Therefore, it is necessary to modify this type of proton exchange membrane. Among the many modification methods, one of the more effective and economical methods is to add water-soluble positively charged polymer additives to the electrolyte. However, a large number of experiments have shown that after a long period of circulation, this type of polymer additive will gradually desorb from the surface of the proton exchange membrane and accumulate on the electrode of the vanadium battery, causing the electrode performance to gradually deteriorate, and ultimately leading to a gradual decrease in the coulombic efficiency and voltage efficiency of the battery. Therefore, finding a low-cost, high ion selectivity, high ion conductivity vanadium battery separator and its modification method has become one of the hot topics in the field of vanadium batteries. Summary of the invention
[0003] In view of the above problems or shortcomings, the present invention provides a vanadium battery diaphragm assembly with a three-layer membrane structure and a preparation method thereof. The technical solution adopted by the present invention is as follows:
[0004] A method for preparing a vanadium battery diaphragm assembly with a three-layer membrane structure, comprising at least the following steps:
[0005] Step S1: weighing 0.5-10 parts by weight of water-soluble high molecular polymer modified polyvinyl pyrrolidone and adding it to 90-99.5 parts by weight of deionized water, stirring to dissolve it, and obtaining a polymer aqueous solution with a mass fraction of 0.5%-10%;
[0006] Step S2: 0.1~1m 2 The original diaphragm for vanadium battery is immersed in 1-10L polymer aqueous solution for 0.5-10h, and then stored in deionized water to obtain a polymer-modified diaphragm;
[0007] Step S3: stacking the polymer-modified diaphragm between two microfiltration membranes to form a vanadium battery diaphragm combination with a three-layer membrane structure.
[0008] Preferably, the preparation steps of the water-soluble polymer modified polyvinyl pyrrolidone in step S1 are as follows:
[0009] Step S11: Add 3.2 parts by mass of N-vinyl pyrrolidone, 13.6 parts by mass of oily initiator and 0.5-1.0 parts by mass of reversible addition-fragmentation chain transfer reagent into a reaction bottle and mix them evenly; after deoxygenation, place in an oil bath at 60-80°C and react at a speed of 350-600 r / min for 3-5 hours, take out the reactant, add solvent dichloromethane to fully dissolve it, and then slowly pour it into anhydrous ether for precipitation, and filter the obtained solid and freeze-dry it to obtain polyvinyl pyrrolidone;
[0010] Step S12: Add 10-20 parts by mass of deionized water and 0.5-1.0 parts by mass of polyvinyl pyrrolidone into the reactor, add 1.5-3.0 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride monomer after ultrasonic stirring, and then add 0.02-0.04 parts by mass of aqueous initiator, and then stir ultrasonically to uniformly fill with nitrogen to deoxygenate the reaction for protection, heat to 60-80°C, react for 7-12 hours, take out and freeze-dry to obtain a water-soluble polymer modified polyvinyl pyrrolidone.
[0011] Preferably, the reversible addition-fragmentation chain transfer reagent in step S11 is at least one of 2-[(dodecylsulfanyl)thioacyl]-sulfanylpropionic acid, dithiobenzoate, and dithiocarbamate.
[0012] Preferably, the oily initiator in step S11 is at least one of azobisisobutyronitrile, dibenzoyl peroxide, and 4,4'-azo(4-cyanovaleric acid).
[0013] Preferably, the aqueous initiator in step S12 is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.
[0014] Preferably, the original diaphragm for the vanadium battery in step S2 is a fluorinated sulfonic acid proton exchange membrane.
[0015] Preferably, the two microfiltration membranes in step S3 are at least one of polyethersulfone membrane, polyvinylidene fluoride membrane, polyacrylonitrile membrane and polyamide membrane.
[0016] Preferably, in step S3, the pore size of the microfiltration membrane is 0.05-0.45 μm, and the thickness is 20-120 μm.
[0017] A vanadium battery diaphragm combination with a three-layer membrane structure is prepared by the above-mentioned method for preparing a vanadium battery diaphragm combination with a three-layer membrane structure.
[0018] The beneficial effects of the present invention include at least:
[0019] 1. The water-soluble high molecular polymer modified polyvinyl pyrrolidone prepared by the present invention is adsorbed on the surface of the original diaphragm under the attraction of sulfonate radicals to form a polymer adsorption layer. The adsorption layer is positively charged and has a repulsive effect on vanadium ions, thereby reducing the shuttling of vanadium ions.
[0020] 2. In the vanadium battery diaphragm combination of the three-layer membrane structure of the present invention, the microfiltration membrane has a pore size much larger than that of hydrogen ions, so it does not affect the transmission of protons. At the same time, the pore size of the microfiltration membrane is small enough compared to the water-soluble high molecular polymer, which can prevent the high molecular polymer adsorbed on the diaphragm from being desorbed from the diaphragm and passing through the microfiltration membrane to be permanently adsorbed by the electrode, making the electrode inert. During the battery cycle, the water-soluble high molecular polymer permanently forms a vanadium-blocking polymer adsorption layer on the initial diaphragm for vanadium batteries;
[0021] 3. Compared with hydrated vanadium ions, the pore size of the microfiltration membrane is smaller. Based on the pore size screening effect, it can also prevent the positive and negative vanadium ions from intermingling to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The diagram is a preparation mechanism diagram of water-soluble high molecular polymer modified polyvinyl pyrrolidone in Example 1 of the present invention;
[0023] Figure 2 A schematic structural diagram of a vanadium battery diaphragm assembly with a three-layer membrane structure and a preparation method thereof according to the present invention;
[0024] Figure 3 The infrared spectra of polyvinyl pyrrolidone and modified polyvinyl pyrrolidone in Example 1 of the present invention are shown in FIG.
[0025] Reference numerals: 1, microfiltration membrane; 2, original diaphragm of vanadium battery; 3, polymer adsorption layer on the surface of diaphragm; DETAILED DESCRIPTION
[0026] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Referring to the technical solution of the present invention, Figure 1As shown, polyvinyl pyrrolidone is first prepared by reversible addition-fragmentation chain transfer living free radical polymerization, and then methacryloyloxyethyl trimethyl ammonium chloride is added for further reaction to prepare water-soluble polymer-modified polyvinyl pyrrolidone, the water-soluble polymer-modified polyvinyl pyrrolidone is added to deionized water, stirred to dissolve it, and a polymer aqueous solution is obtained, the original diaphragm for vanadium battery is immersed in the polymer aqueous solution, and then stored in deionized water after immersion to obtain a polymer-modified diaphragm, and the polymer-modified diaphragm is stacked between two microfiltration membranes to form a vanadium battery diaphragm combination with a three-layer membrane structure, as shown in the attached Figure 2 As shown, there are microfiltration membranes 1 on both sides, an original diaphragm 2 for vanadium batteries in the middle, and a polymer adsorption layer 3 on the surface of the original diaphragm 2 for vanadium batteries.
[0028] Embodiment 1:
[0029] A method for preparing a vanadium battery diaphragm assembly with a three-layer membrane structure, comprising at least the following steps:
[0030] Step S1: Weigh 0.5 parts by mass of water-soluble high molecular polymer modified polyvinyl pyrrolidone and add it to 99.5 parts by mass of deionized water, stir to dissolve it, and obtain a polymer aqueous solution with a mass fraction of 0.5%;
[0031] Step S2: 0.1m 2 The perfluorosulfonic acid proton exchange membrane for vanadium battery is immersed in 1L polymer aqueous solution for 10 hours, and then stored in deionized water to obtain a polymer-modified perfluorosulfonic acid proton exchange membrane;
[0032] Step S3: pasting or stacking the polymer-modified perfluorosulfonic acid proton exchange membrane between two polyvinylidene fluoride microfiltration membranes with a thickness of 120 μm and a pore size of 0.45 μm to form a vanadium battery diaphragm assembly with a three-layer membrane structure;
[0033] The method for preparing water-soluble high molecular polymer modified polyvinyl pyrrolidone in step S1 at least comprises the following steps:
[0034] Step S11: Add 3.2 parts by mass of N-vinyl pyrrolidone, 13.6 parts by mass of oily initiator azobisisobutyronitrile and 0.5 parts by mass of reversible addition-fragmentation chain transfer reagent 2-[(dodecylsulfanyl)thioacyl]-sulfanylpropionic acid into a reaction bottle and mix them evenly; after deoxygenation, place in a 60°C oil bath at a speed of 350 r / min for 3 h, take out the reactant, add solvent dichloromethane to fully dissolve it, and then slowly pour it into anhydrous ether for precipitation. The obtained solid is filtered and freeze-dried to obtain polyvinyl pyrrolidone;
[0035] Step S12: adding 10 parts by mass of deionized water and 0.5 parts by mass of polyvinyl pyrrolidone into the reactor, adding 1.0 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride monomer after ultrasonic stirring, and then adding 0.02 parts by mass of aqueous initiator ammonium persulfate, stirring evenly by ultrasonic stirring, filling with nitrogen to deoxygenate for protection reaction, heating to 60° C., reacting for 7 hours, taking out and freeze-drying, and obtaining water-soluble polymer modified polyvinyl pyrrolidone;
[0036] like Figure 3 As shown in the figure, the infrared spectra of modified polyvinyl pyrrolidone before and after modification are compared. -1 、1160cm -1 、952cm -1 There is a clear absorption peak at the two locations, which are the absorption peak of C=O on the ester group in the methacryloyloxyethyltrimethylammonium chloride molecule, the absorption peak of COC on the ester group and the absorption peak of CN in the quaternary ammonium salt. The above results indicate that it has been successfully embedded into the polyvinylpyrrolidone molecule.
[0037] Embodiment 2:
[0038] A method for preparing a vanadium battery diaphragm assembly with a three-layer membrane structure, comprising at least the following steps:
[0039] Step S1: Weigh 2 parts by mass of water-soluble high molecular weight polymer modified polyvinyl pyrrolidone and add it to 98 parts by mass of deionized water, stir to dissolve it, and obtain a polymer aqueous solution with a mass fraction of 2%;
[0040] Step S2: 0.2m 2 The perfluorosulfonic acid proton exchange membrane for vanadium battery is immersed in 5L polymer aqueous solution for 4 hours, and then stored in deionized water to obtain a polymer-modified perfluorosulfonic acid proton exchange membrane;
[0041] Step S3: pasting or stacking the polymer-modified perfluorosulfonic acid proton exchange membrane between two polyethersulfone microfiltration membranes with a thickness of 80 μm and a pore size of 0.22 μm to form a vanadium battery diaphragm combination with a three-layer membrane structure;
[0042] The method for preparing water-soluble high molecular polymer modified polyvinyl pyrrolidone in step S1 at least comprises the following steps:
[0043] Step S11: Add 3.2 parts by mass of N-vinyl pyrrolidone, 13.6 parts by mass of oily initiator azobisisobutyronitrile and 0.6 parts by mass of reversible addition-fragmentation chain transfer reagent 2-[(dodecylsulfanyl)thioacyl]-sulfanylpropionic acid into a reaction bottle and mix them evenly; after deoxygenation, place in a 70°C oil bath at a speed of 400 r / min for 3.5 hours, take out the reactant, add solvent dichloromethane to fully dissolve it, and then slowly pour it into anhydrous ether for precipitation, and filter the obtained solid and freeze-dry it to obtain polyvinyl pyrrolidone;
[0044] Step S12: Add 14 parts by mass of deionized water and 0.6 parts by mass of polyvinyl pyrrolidone into the reactor, add 1.5 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride monomer after ultrasonic stirring, and then add 0.03 parts by mass of aqueous initiator potassium persulfate, and after ultrasonic stirring, fill with nitrogen to deoxygenate for protection reaction, heat to 70°C, react for 8 hours, take out and freeze-dry, and obtain water-soluble polymer modified polyvinyl pyrrolidone.
[0045] Embodiment 3:
[0046] A method for preparing a vanadium battery diaphragm assembly with a three-layer membrane structure, comprising at least the following steps:
[0047] Step S1: Weigh 5 parts by mass of water-soluble high molecular polymer modified polyvinyl pyrrolidone and add it to 95 parts by mass of deionized water, stir to dissolve it, and obtain a polymer aqueous solution with a mass fraction of 5%;
[0048] Step S2: 0.5m 2 The perfluorosulfonic acid proton exchange membrane for vanadium battery was immersed in 8L polymer aqueous solution for 2 h, and then stored in deionized water to obtain a polymer-modified perfluorosulfonic acid proton exchange membrane.
[0049] Step S3: pasting or stacking the polymer-modified perfluorosulfonic acid proton exchange membrane between two polyacrylonitrile microfiltration membranes with a thickness of 50 μm and a pore size of 0.15 μm to form a vanadium battery separator assembly with a three-layer membrane structure;
[0050] The method for preparing water-soluble high molecular polymer modified polyvinyl pyrrolidone in step S1 at least comprises the following steps:
[0051] Step S11: Add 3.2 parts by mass of N-vinyl pyrrolidone, 13.6 parts by mass of oily initiator dibenzoyl peroxide and 0.8 parts by mass of reversible addition-fragmentation chain transfer reagent dithiobenzoate into a reaction bottle and mix them evenly; after deoxygenation, place in a 75°C oil bath at a speed of 500 r / min for 4.5 hours, take out the reactant, add solvent dichloromethane to fully dissolve it, and then slowly pour it into anhydrous ether for precipitation, and filter the obtained solid and freeze-dry it to obtain polyvinyl pyrrolidone;
[0052] Step S12: Add 17 parts by mass of deionized water and 0.8 parts by mass of polyvinyl pyrrolidone into the reactor, add 2.5 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride monomer after ultrasonic stirring, and then add 0.03 parts by mass of aqueous initiator potassium persulfate, and after ultrasonic stirring, fill with nitrogen to deoxygenate for protection reaction, heat to 75°C, react for 10 hours, take out and freeze-dry, and obtain water-soluble polymer modified polyvinyl pyrrolidone.
[0053] Embodiment 4:
[0054] A method for preparing a vanadium battery diaphragm assembly with a three-layer membrane structure, comprising at least the following steps:
[0055] Step S1: Weigh 10 parts by weight of water-soluble high molecular polymer modified polyvinyl pyrrolidone and add it to 90 parts by weight of deionized water, stir to dissolve it, and obtain a polymer aqueous solution with a mass fraction of 10%;
[0056] Step S2: 1m 2 The perfluorosulfonic acid proton exchange membrane for vanadium battery was immersed in 10L polymer aqueous solution for 0.5 h, and then stored in deionized water to obtain a polymer-modified perfluorosulfonic acid proton exchange membrane.
[0057] Step S3: pasting or stacking the polymer-modified perfluorosulfonic acid proton exchange membrane between two polyamide microfiltration membranes with a thickness of 20 μm and a pore size of 0.05 μm to form a vanadium battery separator assembly with a three-layer membrane structure;
[0058] The method for preparing water-soluble high molecular polymer modified polyvinyl pyrrolidone in step S1 at least comprises the following steps:
[0059] Step S11: Add 3.2 parts by mass of N-vinyl pyrrolidone, 13.6 parts by mass of oily initiator 4,4'-azo (4-cyanovaleric acid) and 1 part by mass of reversible addition-fragmentation chain transfer reagent dithiocarbamate into a reaction bottle and mix them evenly; after deoxygenation, place in an 80°C oil bath at a speed of 600 r / min for 5 hours, take out the reactant, add solvent dichloromethane to fully dissolve it, and then slowly pour it into anhydrous ether for precipitation, and filter the obtained solid and freeze-dry it to obtain polyvinyl pyrrolidone;
[0060] Step S12: Add 20 parts by mass of deionized water and 1 part by mass of polyvinyl pyrrolidone into the reactor, add 3 parts by mass of methacryloyloxyethyl trimethyl ammonium chloride monomer after ultrasonic stirring, and then add 0.04 parts by mass of aqueous initiator potassium persulfate, and then stir ultrasonically to uniformly perform nitrogen deoxygenation protection reaction, heat to 80°C, react for 12 hours, take out and freeze-dry, and obtain water-soluble polymer modified polyvinyl pyrrolidone.
[0061] Comparative Example 1:
[0062] A blank perfluorosulfonic acid membrane was stacked between two polyethersulfone microfiltration membranes with a pore size of 0.22 μm and a thickness of 80 μm to form a vanadium battery membrane combination with a three-layer membrane structure.
[0063] Comparative Example 2:
[0064] The preparation process is consistent with that of Example 2, except that step S3 is not performed, that is, microfiltration membranes are not placed on both sides of the polymer-modified diaphragm.
[0065] The three-layer membrane structure vanadium battery separator assembly made in Examples 1 to 4 and Comparative Examples 1 to 2 was assembled on a battery stack for testing. The coulombic efficiency, voltage efficiency, and energy efficiency at the 10th and 500th cycles were tested and recorded under the same test conditions. The test results are shown in Table 1:
[0066] Table 1 Battery performance test table
[0067]
[0068] As shown in Table 1, Examples 1-4 have higher coulombic efficiency at the 10th cycle and the 500th cycle compared to Comparative Example 1, because the water-soluble polymer modified polyvinyl pyrrolidone prepared by the present invention is adsorbed on the surface of the original diaphragm under the attraction of sulfonate radicals to form a polymer adsorption layer, which is positively charged and has a repulsive effect on vanadium ions, thereby reducing the shuttling of vanadium ions. Examples 1-4 also have higher coulombic efficiency at the 10th cycle and the 500th cycle compared to Comparative Example 2, because the pore size of the microfiltration membrane is smaller than that of the hydrated vanadium ions, and according to the pore size screening effect, it can also prevent the positive and negative vanadium ions from inter-connecting to a certain extent. In addition, compared with Comparative Example 2, Examples 1-4 have higher voltage efficiency and energy efficiency at the 500th cycle. This is because the pore size of the microfiltration membrane is much larger than that of hydrogen ions, which does not affect the transmission of protons. At the same time, the pore size of the microfiltration membrane is small enough compared to the water-soluble polymer, which can prevent the polymer adsorbed on the diaphragm from being desorbed from the diaphragm and passing through the microfiltration membrane to be permanently adsorbed by the electrode, making the electrode inert. During the battery cycle, the water-soluble polymer permanently forms a vanadium-blocking polymer adsorption layer on the initial diaphragm for vanadium batteries.
[0069] In summary, the present invention provides a vanadium battery diaphragm combination with a three-layer membrane structure and a preparation method thereof, that is, a diaphragm modification method that combines water-soluble high molecular polymer modified polyvinyl pyrrolidone with the screening effect of a microfiltration membrane, which improves the ion selectivity, long-term cycle stability and mechanical properties of the diaphragm without affecting the ion conductivity of the diaphragm, and also avoids the problem of significantly increased costs caused by various complex modifications.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a vanadium battery diaphragm assembly with a three-layer membrane structure, characterized in that: At least the following steps are included: Step S1: Weigh 0.5-10 parts by weight of water-soluble polymer-modified polyvinyl pyrrolidone and add it to 90-99.5 parts by weight of deionized water, stir to dissolve it, and obtain a polymer aqueous solution with a mass fraction of 0.5%-10%; the preparation steps of the water-soluble polymer-modified polyvinyl pyrrolidone are as follows: Step S11: Add 3.2 parts by mass of N-vinyl pyrrolidone, 13.6 parts by mass of oily initiator and 0.5-1.0 parts by mass of reversible addition-fragmentation chain transfer reagent into a reaction bottle and mix them evenly; after deoxygenation, place in an oil bath at 60-80°C and react at a speed of 350-600r / min for 3-5h, take out the reactant, add solvent dichloromethane to fully dissolve it, and then slowly pour it into anhydrous ether for precipitation, and filter the obtained solid and freeze-dry it to obtain polyvinyl pyrrolidone; Step S12: adding 10-20 parts by weight of deionized water and 0.5-1.0 parts by weight of polyvinyl pyrrolidone into a reactor, adding 1.5-3.0 parts by weight of methacryloyloxyethyl trimethyl ammonium chloride monomer after ultrasonic stirring, and then adding 0.02-0.04 parts by weight of aqueous initiator, and then ultrasonic stirring for uniformity, nitrogen filling and deoxygenation protection reaction, heating to 60-80° C., reacting for 7-12 hours, taking out and freeze drying, and obtaining a water-soluble polymer modified polyvinyl pyrrolidone; Step S2: 0.1~1m 2 The original diaphragm for vanadium battery is soaked in 1-10L polymer aqueous solution for 0.5-10h, and then stored in deionized water to obtain a polymer-modified diaphragm; the original diaphragm for vanadium battery is a fluorinated sulfonic acid proton exchange membrane; Step S3: stacking the polymer-modified diaphragm between two microfiltration membranes to form a vanadium battery diaphragm combination with a three-layer membrane structure.
2. The method for preparing a three-layer membrane structure vanadium battery separator assembly according to claim 1, characterized in that: In the step S11, the reversible addition-fragmentation chain transfer reagent is at least one of 2-[(dodecylsulfanyl)thioacyl]-sulfanylpropionic acid, dithiobenzoate, and dithiocarbamate.
3. The method for preparing a three-layer membrane structure vanadium battery separator assembly according to claim 1, characterized in that: In the step S11, the oily initiator is at least one of azobisisobutyronitrile, dibenzoyl peroxide, and 4,4'-azo(4-cyanovaleric acid).
4. The method for preparing a three-layer membrane structure vanadium battery separator assembly according to claim 1, characterized in that: The aqueous initiator in step S12 is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.
5. The method for preparing a three-layer membrane structure vanadium battery separator assembly according to claim 1, characterized in that: In step S3, the two microfiltration membranes are at least one of polyethersulfone membrane, polyvinylidene fluoride membrane, polyacrylonitrile membrane and polyamide membrane.
6. The method for preparing a three-layer membrane structure vanadium battery separator assembly according to claim 1, characterized in that: In step S3, the pore size of the microfiltration membrane is 0.05-0.45 μm, and the thickness is 20-120 μm.
7. A vanadium battery diaphragm combination with a three-layer membrane structure, characterized in that: The combination is prepared by the method for preparing a vanadium battery diaphragm combination with a three-layer membrane structure as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Polyolefin double-layer protective ion exchange membrane, preparation method thereof and redox flow battery
CN103985890A
Application of hydrophilic-modified porous diaphragm in flow battery
CN105226222A
Method for preparing hydrophilic polypropylene hollow fiber film with anti-bacterial function
CN106422820A
Vinyl pyrrolidone block copolymer as well as preparation method and application thereof
CN116622039A